Geospatial panorama of long-term care facilities in Brazil: a portrait of territorial inequalities - Tatiana Teixeira Barral de Lacerda; Ana Paula Miranda Neves; Giselle Layse Andrade Buarque; Denise Cuoghi de Carvalho Veríssimo Freitas; Mariana Medeiros Mota Tessarolo; Newton González; Silvio Fernando Barbieri; Ana Amélia Camarano; Karla Cristina Giacomin; Paulo José Fortes Villas Boas (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVES: To map the number and geospatial distribution of Brazilian long-term care facilities (LTCFs) for older adults. Additionally, we sought to highlight the relationship between these findings and the number of older people in the country's 27 Federation Units, demonstrating the growth of these facilities in the last decade. METHODS: This is a descriptive observational study, using secondary data, which was performed in 3 stages: 1) searching and consolidating national and subnational data from different sources and mapping LTCFs; 2) preparing a geospatial map using Brazilian postal codes; and 3) triangulating the number of facilities and of older people in each state and all 5 Brazilian regions. RESULTS: We found 7029 LTCFs in the country, mostly in the Southeast and South regions: São Paulo, Minas Gerais and Rio Grande do Sul had the highest numbers of facilities while states in the North region represented only 1.12% of Brazilian LTCFs. Geospatial mapping highlighted that 64% of the 5 570 Brazilian municipalities did not have any LTCFs for older adults. CONCLUSIONS: We observed a large difference between Brazilian regions regarding the provision of long-term care.